2014
DOI: 10.4049/jimmunol.1302148
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Th1 and Th2 Cytokines in Autotoxicity Driven by CD19-Specific Second-Generation Chimeric Antigen Receptor T Cells in a Mouse Model

Abstract: T cells engrafted with chimeric AgRs (CAR) are showing exciting potential for targeting B cell malignancies in early-phase clinical trials. To determine whether the second-generation CAR was essential for optimal antitumor activity, two CD28-based CAR constructs targeting CD19 were tested for their ability to redirect mouse T cell function against established B cell lymphoma in a BALB/c syngeneic model system. T cells armed with either CAR eliminated A20 B cell lymphoma in vivo; however, one construct induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…However, a recent study from our group has reported short-term Th1-biased cytokine driven toxicity in mice receiving mouse CD19 targeted, second-generation CAR T cells and also reported a chronic toxicity resulting from the specific expansion of myeloid cells in response to Th2-biased cytokine production arising from chronic CD4 + CAR T-cell activity [41]. In this system, acute toxicity manifested as rapid weight loss and cachexia with death occurring 1-5 days after adoptive T-cell transfer.…”
Section: Car T-cell Toxicity In Preclinical Modelsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, a recent study from our group has reported short-term Th1-biased cytokine driven toxicity in mice receiving mouse CD19 targeted, second-generation CAR T cells and also reported a chronic toxicity resulting from the specific expansion of myeloid cells in response to Th2-biased cytokine production arising from chronic CD4 + CAR T-cell activity [41]. In this system, acute toxicity manifested as rapid weight loss and cachexia with death occurring 1-5 days after adoptive T-cell transfer.…”
Section: Car T-cell Toxicity In Preclinical Modelsmentioning
confidence: 93%
“…This third potential mechanism of CAR T-cell toxicity has arisen in experimental models of CAR T-cell therapy recently and relates to the response of non-CAR T cells to the therapy [41]. Prolonged, potentially low level, CAR T-cell activity may indirectly impact upon the local environment resulting in skewing of normal homeostatic cellular responses, that in turn develop into toxicities.…”
Section: Off Target Off Tumor Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…A case reported by Morgan et al showed that activation of anti-ErbB2 CAR-T cells against healthy epithelial tissues that included the lung and heart resulted in the patient's death soon after adoptive transfer . The third potential mechanism of CAR-T cell toxicity may relate to the response of non-CAR-T cells to the therapy (Cheadle et al, 2014). Integrating vectors based upon retroviral and lentiviral backbones may pose a potential risk of oncogenic events.…”
Section: Toxicitymentioning
confidence: 99%
“…However, the Gilham/Hawkins group at the University of Manchester is actively investigating CAR T-cell-mediated toxicity and, in particular, attempting to understand chronic toxicity associated with certain CD19-specific second-generation CARs in syngeneic lymphoma model systems 62 while also working upon improving the in vitro culture conditions used to generate engineered T-cells to improve in vivo functionality. 63 Additionally, the recent arrival of Prof. Mark Exley to Manchester is stimulating work to investigate the efficacy and potency of CARs in iNKT cells.…”
Section: Preclinical Activitymentioning
confidence: 99%